Integração entre a aprendizagem baseada em projetos e o ensino de química: uma proposta para construção da consciência ambiental - Liecheski, Adriane (2019)
The biggest challenge of educators for the beginning of this 21st century is the constant search for innovative methodologies in order to make the citizen critical, reflective, ethical and transformative of society. In this context, this research presents a proposal for the construction of a project that can be applied in the teaching of Chemistry in high school. To this end, we have used the methodology of Project Based Learning (PBL), focusing on the development of Environmental Awareness (EA), and the construction of Chemical Knowledge (CK), in light of the four dimensions, the submicroscopic, macroscopic, symbolic, and human levels. Starting from a real problem, the research has aimed at the use of rainwater by a school. The installation of a cistern to capture rainwater has been proposed. During the execution of the project, several chemical contents were mobilized by the students, it was necessary to assist them in solving the real problem presented. This is a qualitative research, action research as a methodology and it has involved 10 subjects. Data has been collected through the propantion of questionnaires with open and closed questions, as well as the use of Likert scale questions. Data has been tabulated and analyzed in the light of Content Analysis. The results indicate that with the use of PBL there has been evidence of 21st century skills development in students, such as communication, critical thinking, collaboration, creativity, among others. The results also point to the construction of Chemical Knowledge at the four levels of tetrahedron. Through the arguments obtained from the questionnaires, there is a representation of the visible, non-visible, symbolic and human representation. There is evidence that an increase in the degree of Environmental Awareness of the subjects involved has occured. Therefore, the educational product obtained can serve as a guiding tool for high school teachers, in order to integrate the PBL, use its characteristics and terms to promote CK and arouse the EA in the discipline of Chemistry.